Asian-Pacific Journal of Second and Foreign Language Education - Wen, Xu.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Asian-Pacific Journal of Second and Foreign Language Education is an interdisciplinary journal of second and foreign language education studies, a peer-reviewed journal of international scope. It provides a forum for high-quality linguistic and experimental research on topics which investigate applied linguistic theories,second and foreign language learning and teaching. It offers new insights not only into applied linguistics but also into a wide variety of second and foreign language education phenomena. The disciplines covered include applied linguistics, educational linguistics, second language acquisition, foreign language learning and teaching, etc. The journal welcomes authoritative, innovative applied linguistic scholarship from all viewpoints and practices, centered on topics such as: applied linguistics and educational linguistics current approaches to second and foreign language education: topics such as task-based instruction, content-based instruction, big-data-based instruction, and professional communication second and foreign language learning: topics such as motivation, process and mechanism of learning, language aptitude, learning styles and strategies, learning approaches and skills, language transfer, interlanguage, neurobiology of language learning second and foreign language teaching: topics such as teaching methodology, skills for teachers, teacher education, teacher cognition, teacher preparation and professional development, second language assessment, bilingual education course and syllabus design language planning and policy the role of technology in second and foreign language education.
Keywords: Language and languages$1 (BStudy and teaching.s; Applied linguistics; Teachers$1 (BTraining of.s; Language Education; Applied Linguistics; Teaching and Teacher Education